Jaringan Komunikasi Tentang Adopsi Inovasi Tabungan “Simpel” iB (Islamic Banking) SMK Batik Kelas X.A - Yulindha Permatasari (Jurnal Ilmiah Ekonomi Islam, 2019)
"Simple" savings are a new idea among students, so the decision to adopt an innovation requires the role of individuals and social networks. The communication process that occurs between individuals who are members of a group forms a flow of information exchange that is patterned and forms a communication network. As a result of interactions that occur in the communication network there is an exchange of information about innovations which then affect the adoption process. After an analysis, it was concluded that the process of adoption of innovation in SMK BATIK Surakarta was included in the medium and high categories. It can be seen that in the initial stage of knowledge where students of SMK BATIK Surakarta begin to realize the innovation of the "Simple" savings program iB BPR Syariah Syariah Mulia, knowing their functions, benefits and prerequisites, 73% of students at SMK BATIK 1 Surakarta are in the high category, while 27% of group members are in the medium category. After understanding the innovation of the iB BPR Syariah Dana Mulia "Simple" savings program, the next stage of persuasion takes place where students of SMK BATIK 1 Surakarta begin to determine their attitude to accept or reject the innovation of the "Simple" iB BPR Syariah Dana Mulia savings program. The percentage of students who are still hesitant to accept the "Simpel" iB BPR Syariah Dana Mulia savings program is higher than the percentage of students who receive the "Simpel" iB BPR Syariah Dana Mulia savings program